Clinico-Biochemical findings associated with stage III and stage IV of Chronic Kidney Disease in dogs - Vinodhini Jayananthan; Abiramy Prabavathy A; Uma S; Barathiraja S; Rajkumar K; Thanislass J; Vijayalakshmi P (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
The present study on Chronic Kidney Disease (CKD) in dogs was aimed to record the incidence, risk factors, and clinical findings. Dogs irrespective of age, breed, sex with history, and clinical manifestations suggestive of CKD were selected and subjected to physical examination, urinalysis, hematology, and serum biochemistry. Based on these parameters twenty-nine dogs were identified as suffering from CKD and were classified into stage I, stage II, stage III, and stage IV as per the International Renal Interest Society (IRIS) staging system for CKD. Serum biochemistry revealed a significant increase in levels of serum creatinine, BUN, and cholesterol when compared to healthy controls. In conclusion, the prevalence of CKD in dogs was 2.5% and the article discussed the clinical and hemato-biochemical changes in CKD.